Understanding the Model of User Adoption and Acceptance of Technology by Thai Farmers: A Conceptual Framework - Chaveesuk, Singha; Chaiyasoonthorn, Wornchanok; Khalid, Bilal (My University, 2020)
Thailand is constantly making policy changes and implementing Industrial revolution agendas like Thailand 4.0. With the advent of Industry revolution 4.0, Thailand government is making policy initiatives and technological advancement for successful transition to industry 5.0. The initiative is focused to offer farmers an opportunities to incorporate technology in their farming and agricultural processes to produce better crops and high-quality food. The Development of Eastern Economic Corridor is a crucial step in this regard as it focused on the evolution and progression of 10 key industries in Thailand. The plan is designed to be driven through agricultural technology and innovativeness. The future benefits of the ICT based 5.0 industrial revolution in agricultural field directly depends on the user adoption and acceptance of agricultural technology. The study, therefore, investigates the acceptance and adoption of ICT based products and services by farmers by utilizing the basics of TAM. The study proposes the framework of FTAM, and identifies the internal and external factors affecting the behavior intentions and attitude of farmers. It was found out that factors like "occupation relevance", "self-efficacy" and "social influence" affect the "Perceived usefulness (PU)" and "Perceived Ease of Use (PEOU) which in return impact their behavior intention and attitude towards utilizing and accepting ICT based products and services in farming and agriculture.
Keywords: Industrial Revolution; Information Communication Technology; innovativeness; Internet of Things; Perceived Ease of Use; Perceived Usefulness; Technology Acceptance Model